2015
DOI: 10.1111/ijcp.12629
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of erectile dysfunction among patients with sleep disorders: a nationwide population-based cohort study

Abstract: This nationwide cohort study determined that ED risk evidently increased in SD patients compared with the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…O stress e as exigências do trabalho fazem, também, com que os ritmos humanos sejam alterados, tendo consequências diretas nos sistemas orgânicos e no ciclo do sono-vigília, verificando-se também alterações físicas e psicológicas que, consequentemente, condicionam o funcionamento sexual. Os nossos resultados são congruentes com os de outras investigações que demonstram que a qualidade do sono interfere na saúde sexual 8,19,20,21,22,23,24,25,26 pequenas e terem sido realizados com populações clínicas que apresentaram algum tipo de diagnóstico (por exemplo, diabetes ou depressão). Assim, o nosso estudo tem duas grandes contribuições: primeiro, apresenta uma dimensão amostral elevada, quando comparada com outros estudos, e, segundo, foi realizado na população normativa, sem doenças ou comorbilidades associadas.…”
Section: Discussionunclassified
“…O stress e as exigências do trabalho fazem, também, com que os ritmos humanos sejam alterados, tendo consequências diretas nos sistemas orgânicos e no ciclo do sono-vigília, verificando-se também alterações físicas e psicológicas que, consequentemente, condicionam o funcionamento sexual. Os nossos resultados são congruentes com os de outras investigações que demonstram que a qualidade do sono interfere na saúde sexual 8,19,20,21,22,23,24,25,26 pequenas e terem sido realizados com populações clínicas que apresentaram algum tipo de diagnóstico (por exemplo, diabetes ou depressão). Assim, o nosso estudo tem duas grandes contribuições: primeiro, apresenta uma dimensão amostral elevada, quando comparada com outros estudos, e, segundo, foi realizado na população normativa, sem doenças ou comorbilidades associadas.…”
Section: Discussionunclassified
“…Finally, the classification of sexual risk here did not account for the individual’s PrEP status nor the HIV status of the casual partner with respect to viral load detectability or PrEP usage. Finally, we did not assess for clinical sleep problems or other physical conditions which may be associated with reduced sexual activity (e.g., Allen & Desille, 2017; Budweiser et al, 2009; Lin et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Leaving aside clinical studies linking chronic sleep disorders with reduced sexual functioning (e.g., Allen & Desille, 2017; Kling et al, 2017; Budweiser et al, 2009; Lin et al, 2015), we are aware of only five studies that have considered tiredness or poor sleep in connection with increased sexual interest, behavior, and/or risk-taking. Two experimental studies have shown that sleep deprivation led men to pay greater attention to images of attractive women (Zarcone, de la Pena, & Dement, 1974), and that poorer overall sleep quality in women was associated with greater sexual arousal after an induced sexual fantasy exercise (Costa & Oliveira, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of chronic diseases, including diabetes, hypertension, cardiovascular disease (CVD), chronic renal failure, and depression, were also shown to be related to ED [5]. Recently, our studies showed that gout [6] and sleep disorder [7] were also strongly associated with ED. Ischemic heart disease is associated with ED, which in turn is deemed as an efficient predictor of ischemic heart disease [8].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, according to the nationwide population-based cohort study which examined 34,548 sleep disorder (SD) patients with a follow-up period of approximately 250,000 person-years, it was discovered that SD patients are at a 2.11-fold increased risk of developing ED, compared with the general population [7].…”
Section: Introductionmentioning
confidence: 99%